Assessment of Cardiometabolic Risk Factors in Viral Liver Cirrhosis: A Systematic Literature Review - Soliyeva Kamola (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
The traditional hepatocentric paradigm of viral liver cirrhosis fundamentally underestimates the profound systemic consequences of chronic viral infection, particularly its impact on the cardiovascular and metabolic networks. This systematic analytical review rigorously evaluates the prevalence, pathogenic mechanisms, and prognostic implications of cardiometabolic risk factors explicitly within the context of Hepatitis B and C virus-induced cirrhosis. Synthesizing empirical data from 15 high-impact multinational and regional cohorts published between 2018 and 2025, the investigation completely dismantles the classical "auto-protection" myth, which erroneously assumed that cirrhosis-induced hypocholesterolemia mitigates cardiovascular events. The aggregated mathematical models demonstrate that the Hepatitis C virus operates as a direct metabolic disruptor, independently increasing the risk of severe insulin resistance (HOMA-IR > 3.8) by a factor of 2.6 compared to non-viral etiologies. The empirical analysis exposes a distinct "lipid paradox" where absolute cholesterol levels decline as hepatic synthetic function fails, yet the concentration of highly atherogenic oxidized low-density lipoproteins (ox-LDL) sharply escalates due to unchecked systemic oxidative stress. Furthermore, the review identifies cirrhotic cardiomyopathy—characterized by latent diastolic dysfunction and QTc interval prolongation (>440 ms)—as a dominant, silent cardiovascular threat present in 48.5% of decompensated patients. The structural findings mandate an immediate paradigm shift in clinical management, dictating the integration of specialized echocardiographic screening and insulin resistance profiling into standard hepatology protocols. Addressing these covert cardiometabolic vectors is the singular viable strategy to optimize survival trajectories and prevent sudden cardiac death in the viral cirrhosis demographic.